Konsep Pendidikan pada Perspektif Supir Truk - Umu Fadilah; Muslimah Nur Tria Sari; Muhammad Iskandar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Education is a basis for someone to achieve success in a career and in society, especially in the small sphere, namely the family which is the basis for someone to continue in the future, thus education is very important to direct someone to everything good, such as in the spiritual field. and social and personal. Related to the Basic Concept of Education in the Perspective of a Truck Driver which focuses on youth whose parents own a truck, in the village of Negara Batin 1, North Sungkai District, North Lampung Regency, Lampung Province. This study aims to determine the understanding of education in young people who choose to continue their parents' work, namely truck drivers and stop continuing their education, so these factors greatly affect the basis of education in order to get a better job. This study uses a qualitative method with the topic instrument studied using data collection techniques, which is carried out by combining, the data analysis is inductive/qualitative, the results of this qualitative research will focus more on knowledge of certain meanings. Based on the results of interviews and observations on the youth of truck drivers, it was found that there was a cause for the cessation of their education so they chose to become truck drivers and continued their parents' work.